Analisis Tingkat Pengetahuan Remaja Tentang Kanker Payudara Pada Siswa/I SMAN 1 Jasinga - Pratama, Dena Adistiya; Sari, Triyana (Universitas Islam Negeri Alauddin Makassar, 2025)
Breast cancer is one of the major health problems that not only affects adult women but also increasingly threatens the adolescent population. Limited knowledge regarding risk factors, signs and symptoms, as well as preventive efforts makes adolescents a vulnerable group. This study aims to describe the level of knowledge about breast cancer among students at SMAN 1 Jasinga. This research employed a cross-sectional design with a descriptive approach. The sample included all students who met the inclusion criteria using a total sampling technique, with 290 respondents in total. The research instrument was a questionnaire tested for validity and reliability, with knowledge levels categorized into good, fair, and poor. The results showed that 52.8% of respondents had good knowledge, 45.9% had fair knowledge, and 1.4% had poor knowledge. Good knowledge was more frequently found among female students (46.2%) compared to male students (6.6%). In addition, the majority of respondents with good knowledge were grade XII students, indicating the influence of longer learning experiences and greater exposure to health information compared to grades X and XI. In conclusion, most adolescents demonstrated a relatively good level of knowledge about breast cancer, although gaps remain in understanding risk factors, symptoms, and preventive measures. Therefore, continuous health education, particularly through schools and digital media, is essential to enhance adolescents’ awareness of early detection of breast cancer.